ASIATIC LILY FLOWER AS A SOURCE OF PARTY CLOTHING CREATION IDEAS - Salsabillah, Laylisa; Yulistiana, Yulistiana (Home Economics Journal, 2024)
The Asiatic lily flower has a unique beauty, its bright colors, large and curved petals are very eye-catching. The purpose of writing this article is to describe the process of making and finished party clothing using the idea of the Asiatic Lily flower as a detail of manipulating fabric. The method used is the double diamond model, which consists of 4 stages, namely the discover stage by searching, finding and collecting information to be used as a source of ideas. The define stage is defining the information that has been obtained at the discover stage, then expressed in the form of a moodboard. The develop stage, namely the design ideas that have been described through a moodboard, are realized in the form of fashion sketches, and are developed, tested, revised and refined. The deliver stage is analyzing and explaining the results of the finished fashion design from the source of the Asiatic lily flower idea. The resulting party attire is as expected. The application of manipulating asiatic lily flower fabric succeeded in beautifying the appearance. Apart from that, the addition of manipulating fabric cording and the asymmetrical arrangement of manipulating fabric flowers gives a unique impression to party clothing.